Color doppler ultrasound for diagnosis of testicular carcinoma: A comparison with gold standard histopathology. (December 2022) - Fazal, Kamran; fazal, Adnan; siddiqui, Irfan; Mumtaz, Hassan; Basir, Abdul; Butt, Muhammad Meezan; Aman, Muhammad; Khan, Faheemullah; Ahmad, Izaz; Shams, Yumna; Bashir, Anam
Abstract: Introduction: Testicular carcinoma is the most common cancer among males aged 15–34 years. The known risk factors for testicular cancer include undescended testis (cryptorchidism), testicular dysfunction, perinatal factors and prior history of cancer in one testis. We aimed to determine the diagnostic accuracy of color doppler ultrasound in diagnosis of testicular carcinoma using histopathology as GOLD STANDARD. Method: ology: A cross sectional study was conducted from July 2015 to Feb 2016 at the Department of Radiology, Jinnah Post Graduate Medical Center, Karachi. 311 subjects were selected through inpatient/outpatient or emergency department. Patients were evaluated for testicular carcinoma by color doppler ultrasound on Toshiba nemio. Finding of color doppler ultrasound was compared with histopathology. True positive, true negative, false positive, false negative as per operational definition was determined. Results: Mean age of the patients of the study was 41.76 ± 8.11 (30–50) and mean and SD of Duration of symptoms was 5.5 ± 3.5 (4–15) months. Of 175(56.27%) subjects diagnosed as testicular carcinoma on CDUS, only 160(48.55%) were subsequently found to have testicular carcinoma. sensitivity of CDUS in diagnosing scrotal diseases was 88.8% while specificity was 78.1%. Conclusion: We conclude that CDUS is an excellent, safe, and reliable method for evaluating patients with testicular carcinoma. It helps to improve patient's management, especially by preventing unnecessary surgical exploration. It is also convenient and easy to perform. But it has its own limitations, and requires adequate expertise and experience. Its results are also equipment dependent. Highlights: Color Doppler Ultra Sound is a remarkable, secure and trustworthy approach for assessing patients with testicular cancer. It aids in better patient management, particularly by avoiding unnecessary surgical investigation. Appropriate training and experience is required to minimize the negative results.